The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.24059/olj.v20i2.638
|View full text |Cite
|
Sign up to set email alerts
|

Global Times Call for Global Measures: Investigating Automated Essay Scoring in Linguistically-Diverse MOOCs

Abstract: This paper utilizes a case-study design to discuss global aspects of massive open online course (MOOC) assessment. Drawing from the literature on open-course models and linguistic gatekeeping in education, we position freeform assessment in MOOCs as both challenging and valuable, with an emphasis on current practices and student resources. We report on the findings from a linguistically-diverse pharmacy MOOC, taught by a native English speaker, which utilized an automated essay scoring (AES) assignment to enga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 20 publications
0
20
0
2
Order By: Relevance
“…Future studies should continue to utilize different samples to test the validity of the automated VAIL to verify that the current results consistently replicate. In light of recent findings that suggest automated scoring techniques differentially benefit native English speakers (Reilly et al, 2016), it would be advantageous to test the automated VAIL, and similar measures, in linguistically diverse samples to ensure validity. As previously mentioned the present study considered in-service teachers who were enrolled in coursework and/or coaching.…”
Section: Future Directionsmentioning
confidence: 99%
“…Future studies should continue to utilize different samples to test the validity of the automated VAIL to verify that the current results consistently replicate. In light of recent findings that suggest automated scoring techniques differentially benefit native English speakers (Reilly et al, 2016), it would be advantageous to test the automated VAIL, and similar measures, in linguistically diverse samples to ensure validity. As previously mentioned the present study considered in-service teachers who were enrolled in coursework and/or coaching.…”
Section: Future Directionsmentioning
confidence: 99%
“…Nonnative English-speaking students read more slowly than native speakers and are likely to play a video slowly to understand instructors' lessons (Reilly et al, 2016) and may require more time to learn the content, sometimes falling behind (Sanchez-Gordon & Luján-Mora, 2014). Nonnative English-speaking students tend to achieve lower scores than Englishspeaking students in MOOCs (Engle et al, 2015;Reilly et al, 2016) Another concern is nonnative English-speaking learners' participation in social interaction, such as online discussion (Colas et al, 2016). In an analysis of online forum participation in a business course offered in Coursera, Gillani and Eynon (2014) found that European and North American participants not only achieved higher grades in forum participation than those from Asia but were also more visible in online forums, participating in discussions more actively than other participants.…”
Section: Nonnative English-speaking Participants' Learning In Moocsmentioning
confidence: 99%
“…Several researchers have argued that MOOC developers and educators should consider their needs. Because most MOOCs are offered in English (Shah, 2015a), the language barrier is a concern (Colas, Sloep, & Garreta-Domingo, 2016;Reilly et al, 2016;Sanchez-Gordon & Luján-Mora, 2014). Nonnative English-speaking students read more slowly than native speakers and are likely to play a video slowly to understand instructors' lessons (Reilly et al, 2016) and may require more time to learn the content, sometimes falling behind (Sanchez-Gordon & Luján-Mora, 2014).…”
Section: Nonnative English-speaking Participants' Learning In Moocsmentioning
confidence: 99%
See 2 more Smart Citations